Utilization of modern temporary contraceptive methods and its predictors among reproductive-aged women in India: insights from NFHS-5 (2019-21) - Ritik Agrawal; Manisha Mishra; Tanveer Rehman; Gayathri Surendran; Abhinav Sinha; Srikanta Kanungo; Sanghamitra Pati (Frontiers Media S.A., 2023)
Evidence from various studies on modern contraceptive methods shows that the utilization varies greatly. The present study aimed to estimate the magnitude and determinants for temporary modern contraceptive utilization among reproductive-aged (15-49 years) women in India. We analysed National Family Health Survey-5 data using the "svyset" command in STATA software. Modern contraception utilization was estimated using the weighted prevalence, and its correlates were assessed by multivariable regression by reporting an adjusted prevalence ratio (aPR) with 95% confidence interval (CI). QGIS 3.2.1 software was used for spatial analysis of different temporary modern contraceptives. The mean (SD) age of 359,825 respondents was 31.6 (8.5) years with 75.1% (n = 270,311) and 49.2% (n = 177,165) of them being from rural area and having completed education up to secondary school, respectively. The overall utilization of modern temporary contraception was 66.1% [95%CI: 65.90-66.35, n = 237,953]. Multigravida (vs. nulligravida) [aPR = 2.13 (1.98-2.30)], higher education of husband (vs. not educated) [aPR = 1.20 (1.14-1.27)], urban (vs. rural) [aPR = 1.06 (1.03-1.10)], watching television less than once a week (vs. not at all) [aPR = 1.04 (1.01-1.08)], divorced (vs. married) [aPR = 0.65 (0.45-0.94)], and Scheduled Tribe (ST) (vs. unreserved) [aPR = 0.92 (0.88-0.96)] were significant independent determinants. The highest utilization of male condoms, IUCDs, pills and injections were in Himachal Pradesh (86%), Nagaland (64%), Tripura (85%), and Ladakh (20%), respectively. Out of every ten reproductive-aged (15-49 years) women in India, six are using temporary modern contraceptive methods. More intervention strategies should be planned, considering factors like gravida, education, residence, health promotion and caste to attain replacement fertility level.